The extent and meaning of hybridization and introgression between Siberian spruce (Picea obovata) and Norway spruce (Picea abies): cryptic refugia as stepping stones to the west?. Issue 12 (18th May 2016) - Tsuda, Yoshiaki; Chen, Jun; Stocks, Michael; Källman, Thomas; Sønstebø, Jørn Henrik; Parducci, Laura; Semerikov, Vladimir; Sperisen, Christoph; Politov, Dmitry; Ronkainen, Tiina; Väliranta, Minna; Vendramin, Giovanni Giuseppe; et al.
Abstract: Boreal species were repeatedly exposed to ice ages and went through cycles of contraction and expansion while sister species alternated periods of contact and isolation. The resulting genetic structure is consequently complex, and demographic inferences are intrinsically challenging. The range of Norway spruce ( Picea abies ) and Siberian spruce ( Picea obovata ) covers most of northern Eurasia; yet their geographical limits and histories remain poorly understood. To delineate the hybrid zone between the two species and reconstruct their joint demographic history, we analysed variation at nuclear SSR and mitochondrial DNA in 102 and 88 populations, respectively. The dynamics of the hybrid zone was analysed with approximate Bayesian computation (ABC) followed by posterior predictivestructure plot reconstruction and the presence of barriers across the range tested with estimated effective migration surfaces. To estimate the divergence time between the two species, nuclear sequences from two well‐separated populations of each species were analysed with ABC. Two main barriers divide the range of the two species: one corresponds to the hybrid zone between them, and the other separates the southern and northern domains of Norway spruce. The hybrid zone is centred on the Urals, but the genetic impact of Siberian spruce extends further west. The joint distribution of mitochondrial and nuclear variation indicates an introgression of mitochondrial DNA from Norway spruce into Siberian spruce. Overall, our data reveal a demographic history where the two species interacted frequently and where migrants originating from the Urals and the West Siberian Plain recolonized northern Russia and Scandinavia using scattered refugial populations of Norway spruce as stepping stones towards the west.